THE EFFECT OF ECONOMIC GROWTH DETERMINANTS ON ECONOMIC GROWTH: A STUDY ON DIFFERENT FINANCIAL SYSTEMS - JANNATUL FERDAOUS (Journal of Business & Economic Analysis, 2022)
One of the main goals of a country is to achieve economic growth. This has led many researchers to understand and determine the factors that boost economic growth. The relationship between these two still remains to be unanswered. It has been discussed in many kinds of research that the variability could result from the different types of financial systems being observed by different countries. By taking 15 years of data from 32 OECD countries, this study attempted to identify if there is any difference in the effects of the factors of economic growth across two distinct financial systems (bank-based and market-based). The results of the study suggest that, overall, financial system differences influence the economic growth of a country. These insights give further clarification on how the economic growth determinants were acting differently in different countries.